Dermoscopic approach to hypopigmentary or depigmentary lesions in skin of color - Balachandra S Ankad; Varsha R Koti (Wolters Kluwer Medknow Publications, 2020)
Introduction: Hypopigmented or depigmented lesions are considered as important dermatoses in daily practice. Their accurate diagnosis is very much crucial because of social stigma attached to these diseases in Indian subcontinent. Authors have proposed basic guidelines for dermoscopic assessment in terms of approach to a given hypopigmented/depigmented lesion. The following conditions are dermoscopically described here, they are vitiligo, idiopathic guttate hypomelanosis, lichen sclerosus, pityriasis alba, leprosy, pityriasis versicolor and nevus depigmentosus. Aim: To propose basic dermoscopic guidelines in terms of approach of a hypopigmented/ depigmented lesion in skin of color. Summary: Dermoscopic patterns highly depend on melanin skin layers and thus analysis of dermoscopic patterns in hypopigmented/depigmented lesions is difficult owing to the reduction or absent melanin in the epidermis. All hypopigmented/depigmentary conditions are described based on the 5 dermoscopic parameters which include; i) background colour, ii) vessels, iii) scales, iv) follicular findings and v) specific clues. Glowing white color in vitiligo and pale or dull white color in IGH and white with little brownish color in PA and PV are the different shades of color in the background in dermoscopy. In leprosy, PMH and ND, background color is brownish-white rather white. LSEA, color is white with bluish or pinkish hue is observed. Furthermore, dermoscopic diagnosis should be based on every parameter visible in a given lesion and not in isolation as each pattern or parameter is immensely contributory to the final diagnosis. Conclusion: Thus, dermoscopy aids in the distinction of hypopigmented/depigmentary lesions by demonstrating characteristic and definitive patterns.